Robust observed-state feedback design for discrete-time systems rational in the uncertainties. (February 2017) - Peaucelle, Dimitri; Ebihara, Yoshio; Hosoe, Yohei
Abstract: Design of controllers in the form of a state-feedback coupled to a state observer is studied in the context of uncertain systems. The classical approach by Luenberger is revisited. Results provide a heuristic design procedure that mimics the independent state-feedback/observer gains design by minimizing the coupling of observation error dynamics on the ideal state-feedback dynamics. The proposed design and analysis conditions apply to linear systems rationally-dependent on uncertainties defined in the cross-product of polytopes. Convex linear matrix inequality results are given thanks to the combination of a descriptor multi-affine representations of systems and the S -variable approach. Stability and H ∞ performances are assessed by multi-affine parameter-dependent Lyapunov matrices.